2011
DOI: 10.1016/j.ejcts.2011.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile pulmonary perfusion with oxygenated blood ameliorates pulmonary hemodynamic and respiratory indices in low-risk coronary artery bypass patients☆

Abstract: Oxygenated blood PPP proved safe and significantly ameliorated pulmonary hemodynamic parameters and respiratory indices in low-risk CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…As reported in animal studies, [13][14][15][16] small randomised trials and observational studies in infants 18 19 and adults, [22][23][24][25] we have now evaluated and confirmed in a clinical setting with adult patients with COPD, that pulmonary artery perfusion with oxygenated blood during CPB results in a higher postoperative oxygenation. This was obtained without an increased incidence of complications or significant prolongation of the surgical procedure.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…As reported in animal studies, [13][14][15][16] small randomised trials and observational studies in infants 18 19 and adults, [22][23][24][25] we have now evaluated and confirmed in a clinical setting with adult patients with COPD, that pulmonary artery perfusion with oxygenated blood during CPB results in a higher postoperative oxygenation. This was obtained without an increased incidence of complications or significant prolongation of the surgical procedure.…”
Section: Discussionmentioning
confidence: 54%
“…It has now been confirmed in several animal models that bronchial artery blood flow is decreased substantially during CPB, and although exposure to CPB alone is enough to cause pulmonary injury, concomitant cessation of pulmonary artery flow contributes significantly to the development of postoperative pulmonary dysfunction. [9][10][11][12] The results of animals studies, [13][14][15][16] small randomised trials in infants with congenital heart disease 17-20 and inconclusive minor randomised trials and observational studies in adults [21][22][23][24][25] indicates that pulmonary artery perfusion with normothermic oxygenated blood preserves postoperative oxygenation. Further, lung transplantation experiences has shown that pulmonary artery perfusion with a hypothermic preservation solution protects the lungs from warm ischaemic injury during storage and transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the contact of blood with artificial surfaces of the CPB circuit, lung ischemia/reperfusion injury, and intraoperative CPB-associated nonphysiologic linear perfusion play a major role in triggering pulmonary and systemic inflammatory responses. A recent study of pulsatile pulmonary perfusion reported its beneficial effect on pulmonary hemodynamic and respiratory functions in low-risk coronary artery bypass patients (3)(4)(5)(6)(7). To our knowledge, this is the first meta-analysis of pulmonary dysfunction with regard to pulsatile perfusion during CPB.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, blood contact with artificial material, lung ischemia/ reperfusion injury, and CPB-induced nonphysiologic linear perfusions are considered the main causes of dysfunction (7).…”
mentioning
confidence: 99%
“…10 In patients, pulmonary indices (alveolo-arterial oxygen delivery, PaO 2 /F I O 2 ratio, and lung compliance) were significantly better preserved when treated with pulsatile pulmonary perfusion during CPB. 13 Postoperative bronchoalveolar lavage specimens showed a lower absolute count of white blood cells and a lower percentage of neutrophils in patients with pulsatile pulmonary perfusion, suggesting that a lower alveolar inflammatory response was present. However, circulating cytokine levels were not significantly different compared with subjects in a control group.…”
Section: Cardiopulmonary Bypassmentioning
confidence: 96%